Individual consultations: Towards a 360-degree evaluation process - Berry, Lynn; Collins, Garry; Copeman, Peter; Harper, Rowena; Li, Linda; Prentice, Susan (Journal of Academic Language and Learning, 2012)
In an era of increasing accountability in higher education, it is critical that academic language and learning (ALL) centres examine the efficacy of their one-to-one teaching in a rigorous and reliable way. The diversity of the ALL context, however, is such that a single set of evaluation instruments is unlikely to be appropriate for every centre. Stevenson and Kokkinn’s (2009) framework is useful here: rather than suggesting a particular methodology or instrument for evaluating one-to-one teaching, the authors instead propose a theoretical framework, a set of considerations relevant for ALL staff when selecting or designing evaluations. This paper reports on the attempt of one ALL centre – the Academic Skills Centre (ASC) at the University of Canberra – to improve its evaluation of one-to-one teaching using Stevenson and Kokkinn’s (2009) framework. Working through its recommended steps, the ASC developed a 360° approach which sought to triangulate feedback gained from three instruments: peer-observations of teaching, self-reflection, and student questionnaires. This therefore incorporated not only student perspectives on teaching, but also those of the academic advisors and their peers. After implementing those instruments, it was found that while student questionnaires remained limited in their capacity to provide useful feedback on teaching, the combination of guided self-reflection and peer observation facilitated significant learning about one-to-one teaching practice, and developed staff teaching strategies. A thorough consideration of Stevenson and Kokkinn’s (2009) four “steps” also produced an evaluation cycle that was multi-faceted and versatile, and able to achieve a range of both internal and external purposes.